2021
DOI: 10.3390/ijerph18157778
|View full text |Cite
|
Sign up to set email alerts
|

Health-Related Fitness Levels among Title I Elementary School Students

Abstract: Over the past few decades, studies have emphasized improving children’s health by increasing health-related fitness levels. Despite the known benefits of health-related fitness in youth, studies have also highlighted a lack of physical activity opportunities for children living in low-income households. The purpose of this study was to investigate the health-related fitness levels of students attending Title I (low-income) elementary schools. A total of 77 elementary students (50.6% female; Mage = 10.0, SD = 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…Furthermore, a number of research studies have shown that low socioeconomic status is associated with physical inactivity and low levels of health-related fitness among school-aged children. Factors such as limited physical activity opportunities, unhealthy eating habits, and environmental stressors disproportionately affect children from economically disadvantaged backgrounds, contributing to poorer health outcomes [5][6][7]. Similarly, Peralta et al's research emphasized the impact of socioeconomic status on physical activity behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a number of research studies have shown that low socioeconomic status is associated with physical inactivity and low levels of health-related fitness among school-aged children. Factors such as limited physical activity opportunities, unhealthy eating habits, and environmental stressors disproportionately affect children from economically disadvantaged backgrounds, contributing to poorer health outcomes [5][6][7]. Similarly, Peralta et al's research emphasized the impact of socioeconomic status on physical activity behaviors.…”
Section: Introductionmentioning
confidence: 99%